PENGABDIAN MASYARAKAT PERTOLONGAN CORPUS ALIENUM MATA PADA PMR DI SMAN 1 PAPAR - damayanti, didit; Siswoaribowo, Andika; Anugrah Anggraini, Devita (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
School life is an important part of children's lives. They spend most of their time at school. The high level of physical activity carried out by school adolescents is one of the factors that cause conditions of foreign body entry in the eye. Accidents or injuries can become emergencies and cause serious injuries and even death if not treated properly. Accidents or injuries can become an emergency case and cause serious injuries and even death if not treated properly. Improving the health status of the school community can be done with a variety of activities, one of which is the provision of Corpus Alienum Eye Aid Training. Students at SMAN I Papar are a group of adolescents in the community who have a risk of health problems due to dynamic activities. First aid for eye injuries due to foreign body entry in the eye (Corpus Alienum in the Eye) can be a treatment that can be given immediately. To prevent the injury from getting worse, Corpus alienum often affects the sclera, cornea, and conjunctiva. Each of these parts can lead to different complications. If a corpus alienum enters the eyeball/oculi, there will be a severe infectious reaction and intraocular damage. Therefore, it is necessary to quickly recognize the object and determine its location for later removal. Community service activities in the form of Corpus Alienum Eye Aid Training at PMR SMAN I Papar is a very positive activity to be carried out in order to disseminate health science so as to increase the knowledge and ability of each student in providing assistance in shoulder dislocation.